2018
DOI: 10.1016/j.bios.2017.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Combination of electrochemical biosensor and textile threads: A microfluidic device for phenol determination in tap water

Abstract: Microfluidic devices constructed using low cost materials presents as alternative for conventional flow analysis systems because they provide advantages as low consumption of reagents and samples, high speed of analysis, possibility of portability and the easiness of construction and maintenance. Herein, is described for the first time the use of an electrochemical biosensor for phenol detection combined with a very simple and efficient microfluidic device based on commercial textile threads. Taking advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 40 publications
1
40
0
3
Order By: Relevance
“…The reflection of such advantages can be seen in its performance, which presents high sensitivity in electroanalytical experiments, high signal-to-noise ratio, possibility of analysis in a short time, and application of electrochemical techniques outside centralized laboratories [14][15][16][17]. For better performance often there is coupling the electrochemical system based on SPEs with nanoscale materials [18] which offers a remarkable wide range of possibilities for regarding new materials used for device construction as well as different applications for the sensors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The reflection of such advantages can be seen in its performance, which presents high sensitivity in electroanalytical experiments, high signal-to-noise ratio, possibility of analysis in a short time, and application of electrochemical techniques outside centralized laboratories [14][15][16][17]. For better performance often there is coupling the electrochemical system based on SPEs with nanoscale materials [18] which offers a remarkable wide range of possibilities for regarding new materials used for device construction as well as different applications for the sensors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, SPEs were also used successfully for implementation of amperometric detection within FIA microfluidic devices based on cotton threads. [76][77][78] The SPEs were easily adapted to these FIA microfluidic devices and used for detection of estriol (LOD = 0.53 μmol L À 1 ) in water samples, [76] phenol (LOD = 0.003 μmol L À 1 ) in tap water" [77] and antioxidants such as gallic (LOD = 1.5 μmol L À 1 ) and caffeic acid (0.8 μmol L À 1 ) in wine. [78] These excellent LODs were obtained with minimal consumption of reagents (flow rate � 0.7 μL s À 1 ) and samples (injection volume = 2.0 μL).…”
Section: Spes Coupled To Fia Systemsmentioning
confidence: 99%
“…Tap water AuSPE modified with SAM and covered of chitosan 1.6 40 [58] Electroactivity of NPs NR SPGE NR NR [59] Isoniazid PF and blood serum SPCE 0.003 50 [60] Arsenic(III) Drinking water SPCE modified with AuNPs and nanofiber-chitosan 0.15 72 [61] Salmonella typhimurium Milk SPCE 7.7 cells mL À 1 NR [ [75] Estriol PF SPCE 0.53 33 [76] Phenol Drinking water SPCE modified with CN/AuNPs/tyrosinase 0.003 30 [77] Gallic acid Caffeic acid Wine SPCE 1.5 08 43 [78] [a] AF: analytical frequency (injections h À 1 ); AuSPE: gold SPE; LOD: limit of detection; NR: not reported; PF: pharmaceutical formulation; SGPE: screen-printed graphite electrode; SPCE: screen-printed carbon electrode; MWCNTSPE: multiwalled carbon nanotube SPE; WE: working electrode; TvL: Trametes versicolor Laccase. and injection valves.…”
Section: -Nitro-p-phenylenediaminementioning
confidence: 99%
“…However, as shown in curve b, there was a quasi-reversible pair of redox peaks with a large cathodic current at 0.05 V (vs. Ag/AgCl) and a small anodic current at 0.45 V (vs. Ag/AgCl). It was indicated that the phenol was first catalyzed to catechol and further catalyzed to o-benzoquinone by Tyr, then electro-reduction of o-benzoquinone and electro-oxidation of some catechol were underwent on the electrode [13,43]. The redox potential of catechol/o-benzoquinone (E 0 = + 0.2 V, vs. Ag/AgCl) was presented as the average value of the potential of anodic and cathodic peaks in the CV [37].…”
Section: Study Of Enzyme Reaction Coupling With Ecc Redox Cyclementioning
confidence: 99%
“…The Tyr is a metalloprotein (EC 1.14.18.1) containing a binuclear copper active that can first catalyze phenol to catechol, and then catechol is converted to o-benzoquinone in the presence of oxygen [10][11][12]. Hence, the most of Tyr based electrochemical sensors are based on the determination of electrochemical reduction of o-benzoquinone [13][14][15].…”
Section: Introductionmentioning
confidence: 99%